The Effectiveness Of Using The Canva App As A Learning Medium IPAS - Sherly, Sherly Carolline Santo (EduGrows: Education and Learning Review, 2025)
The rapid advancement of science and technology in the early 20th century has resulted in information technology and production systems that can be set up automatically. The changes in Industry 4.0 that are taking place in Indonesia have given birth to various technological innovations and caused major transformations in people's social lives. One of the sectors that is most felt because of the implementation of the industrial revolution 4.0 is in the development aspect in the world of education. In the period after the covid-19 pandemic, the role of technology is very dominant in education. Educators and students need technology or platforms that support distance learning activities and still have good interactions, so that the classroom remains not boring or fun and productive. Canva is one of the applications that is able to overcome these challenges. Canva for Education is one of Canva's programs designed specifically to support teaching and learning activities. This service is intended for educators and students to make the learning process more interesting, innovative, and encourage collaboration. The article aims to identify a number of issues that Canva can have with and the extent of its effectiveness as a supporting medium in IPAS learning. Canva is an application that provides various features that support the process of creating learning media by educators, including a variety of templates that can be used in the design process practically. This study uses a literature review approach, with the stages of identifying, accessing, reading, and analyzing a number of literature related to the problem being studied. The data presented in this study comes from the results of a previous study that examined the  Canva's performance as a tool in learning activities.